Integrating ChatGPT into EFL Critical Reading: Effects on Students’ Analytical Thinking - Ilham Sahabuddin; Asriadi Rasyid; Sianna (Faculty of Education and Teacher Training of UIN Palopo, 2026)
This study examined the integration of ChatGPT into critical reading instruction and its association with students’ analytical thinking in an EFL higher education context. The study was motivated by the limited empirical evidence on how ChatGPT supports critical reading skills, particularly in identifying arguments, evaluating evidence, making inferences, comparing perspectives, and constructing analytical responses. A quantitative approach with a pre-experimental one-group pretest-posttest design was employed. The study was conducted at Universitas Muhammadiyah Parepare and involved 10 fourth-semester students of the English Education Study Program enrolled in a Critical Reading course. Data were collected through analytical thinking tests administered before and after the intervention, using a critical reading rubric covering argument identification, fact-opinion distinction, evidence evaluation, inference, perspective comparison, idea connection, and evidence-based response construction. The data were analyzed using descriptive statistics, Shapiro-Wilk normality test, paired sample t-test, normalized gain, and Cohen’s d. The findings showed that the mean score increased from 58.50 in the pretest to 74.50 in the posttest, with a mean gain of 16.00. The normalized gain was 0.39, indicating moderate improvement. The paired sample t-test revealed a significant difference, t(9) = 13.74, p < 0.001, and Cohen’s d = 4.35 indicated a very large effect size. The results indicated that ChatGPT integration was associated with improved students’ analytical thinking in critical reading.